Unpacking the Commodification of Indigenous Rights by Exploring Conditions for Political, Legal, and Moral Agency - Ohlsson, Johanna (Enskilda Högskolan Stockholm, Avdelningen för mänskliga rättigheter och demokrati, 2024)
In the global discourse on Indigenous rights, an increasingly prevalent concern emerges as Indigenous communities navigate the complex intersection of their space for political, legal, and moral agency and various approaches to their rights as Indigenous people. The argument developed in this paper is that when Indigenous rights are seen as interests, privileges, charity or needs rather than rights, they risk being commodified which in turn undermines Indigenous political and moral agency, and this should be understood as a question of recognitional justice. I develop the argument in three steps. The paper sets out to first explore in what contexts, by which actors and to what extent Indigenous rights are being seen as interests, privileges, charity or needs. Focusing on the only Indigenous group within the EU, the Sámi, this paper aims to delineate patterns of commodification, examining how external actors and market forces impact Indigenous rights as well as political, moral, and legal agency. This is based on illustrations from the Sapmiarea of Norway, Finland, and Sweden (c.f. Joona & Joona 2023, Freng Dale & Dannevig 2023). The first section of this exploration delves into the historical context, tracing the roots of the commodification of Indigenous rights. It scrutinizes instances where cultural artefacts, practices, and traditional knowledge have been commodified for economic gain, often without equitable compensation or acknowledgement. The implications of such practices extend beyond economic exploitation, impacting the cultural identity and self-determination of Indigenous groups. Second, the paper elaborates on the argument that approaches to Indigenous rights based on interests, needs, charity, and privileges risk leading to a commodification of Indigenous rights. The commodification of Indigenous rights, often driven by external actors and market forces, poses a significant challenge to the autonomy and self-determination of Indigenous groups worldwide. It also challenges the legitimacy of ...